From Traditional to Digital: Enhancing Teacher Performance for Improved Educational Quality - Supiansyah Supiansyah; Zakky Zamrudi; Husnul Madihah; Siti Fajrianti; Herlina Lusiana (Al-Tanzim: Jurnal Manajemen Pendidikan Islam)
This study aims to analyze digital transformation in improving the quality of education in madrasahs, focusing on optimizing teacher performance. The approach used is qualitative with a case study type, where data is collected through interviews, observations, and documentation. Data are analyzed using reduction, display, and verification, which helps trace the main themes related to technology implementation in learning and teacher professional development. The study results indicate that the application of technology in various aspects, such as online learning platforms, technology training for teachers, and digital tools, can overcome socio-economic challenges and increase teaching effectiveness. Technology allows teachers to access broader and more flexible educational resources and strengthens communication with parents, improving the quality of education in madrasahs. The implications of this study are the importance of integrating technology in education to address socio-economic disparities and improve teacher performance, which will support achieving more inclusive and quality education goals.